A survey of wound care knowledge in South Africa - Coetzee, Francois (Stellenbosch : University of Stellenbosch, 2015)
Abstract Chronic wounds afflict millions worldwide, incurring significant health care costs and chronic suffering. Clinicians are often unsure about treatment, resulting in poor outcomes. Objective To determine the scope of knowledge possessed by fifth year medical students, general practitioners (GP’s) and surgical registrars, concerning chronic wound management. Design Cross sectional study Methods Deans of eight South African medical schools received letters requesting information regarding time devoted to wound-care training. Knowledge-based questionnaires were distributed to final-year students at two universities, surgical registrars at three universities and general practitioners attending refresher courses. Result. Four medical schools replied, of whom only two offered formal teaching. 162 medical students, 45 GP’s and 47 surgical registrars completed questionnaires. The overall median (25th–75th percentiles) knowledge scores for registrars, GP’s and students were 65%;(55%–70%), 55%;(45%–65%) and 45%;(35%–50%) respectively. Whereas the scores of registrars and GP’s did not differ, the student scores were significantly less. Only 32% of registrars and 18% of GP’s attained scores of 70% or more. 96% considered training to be inadequate. Interest in wound-care was only mild to moderate, with more GP’s than registrars requesting literature. Conclusions Very little, if any training on chronic wounds is offered in South Africa. The levels of knowledge cannot be considered adequate for successful treatment, nor for teaching to undergraduates. This preliminary study cannot reflect the attitudes and knowledge throughout the country; however it is clear that there is a need for improved education about these conditions that have huge clinical and economic consequences.